Gastric lethal hemorrhage due to Dieulafoy’s disease - Ponce, Cesar Cilento (Autopsy and Case Reports, 2018)
Gastric Dieulafoy’s lesion (DL) is a potentially fatal entity that causes upper digestive hemorrhage as a consequence of the erosion of an abnormal large-caliber artery in the submucosa of the gastrointestinal tract. We report the case of a 59-year-old female patient admitted to the emergency facility due to melena without any active sign of bleeding during the esophagogastroduodenoscopy. Unexpectedly, she progressed presenting a massive hematemesis followed by an irreversible cardiorespiratory arrest. The aim of this study is to draw attention to DL as a possible cause of massive and fatal digestive hemorrhage, and to describe the anatomical autopsy findings.